Comparison of real-time reverse transcriptase polymerase chain reaction (RT-PCR) and IgM and IgG antibody test for the diagnosis of SARS-CoV-2 infection - ACER, Ömer; ÖZÜDOĞRU, Osman (Jurnal Teknologi Laboratorium, 2020)
In the present study, we compared the real-time reverse-transcription polymerase chain reaction (RT-PCR) and total IgM-IgG antibody tests for diagnosis SARS-CoV-2 patients. SARS-CoV-2 patients were divided into four additional subgroups according to clinical examination, and Computed Tomography (CT) for SARS-CoV-2. Groups were included 60 mild cases, 111 moderate cases, 53 severe cases, and 105 normal cases. In a mild group, 52.5% of 60 cases were found to be male, 45.9% female, and the average age was found as 38.4 ±2.011. The positive ratio was found as 80.3% in the RT-PCR test, while 39.3% in total IgM/IgG. In a moderate group, 49.1% of 111 cases were found to be male, 50% female, and the average age was 45.05 ±1.519. The positive ratio was found as 85.7% in the RT-PCR test while 54.5% in total IgM/IgG. In a severe group, 53.7%of 53 cases were found to be male, 44.4% female, and the average age was 55.5±2.122. The positive ratio was found as 75.9% both in RT-PCR and total IgM/IgG tests. In a normal group with no involvement according to Computed Tomography (CT), 49.1%of 105 cases were found to be male, 50% female, and the average age was found as 34.8±1.391. The positive ratio was found as 95.3% in the RT-PCR test while 5.7% in total IgM/IgG. Chronic diseases were detected more in severe cases, suggesting that persons who have chronic diseases or decreased immunity, such as diabetes mellitus, cardiovascular diseases, hypertension, and lung disease, are at a higher risk for developing severe COVID-19 if they are infected with SARS-CoV-2. According to our results, we can suggest a higher detection sensibility in RT-PCR than in total IgM/IgG antibody test for mild, moderate and normal group, while the detection sensibility of IgM/IgG antibody increases in a severe group with bilateral diffuse involvement according to CT.